Ekoteosentris sebagai Landasan Pencegahan Penebangan Pohon dalam Perspektif Maqasid Syariah: Rekonstruksi Konsep Hifz al-Bi'ah - Ummul Inayah; Nurul Adawia; Azman Arsyad; Lomba Sultan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the relationship between the ecotheocentric paradigm and Maqasid al-Shariah in preventing deforestation while reconstructing the concept of Hifz al-Bi'ah as a normative foundation for environmental protection in Islamic law. The study employs a library research method using a normative-philosophical approach. Data were collected from the Qur'an, Hadith, classical and contemporary Islamic legal literature, books, and relevant scientific journals. The data were analyzed using content analysis through data reduction, classification, interpretation, and conclusion drawing. The findings reveal that the ecotheocentric paradigm views nature as a divine trust endowed with intrinsic value, making environmental conservation an integral part of devotion to Allah. The reconstruction of Hifz al-Bi'ah expands contemporary Maqasid al-Shariah by integrating the principles of tawhid, khilafah, mizan, and islah as the ethical foundation for environmental stewardship. Consequently, preventing deforestation is understood not only as an ecological responsibility but also as a manifestation of religious commitment, moral accountability, and the pursuit of public welfare through sustainable environmental preservation.